Swept Forward Magnetic Field Variability in High‐Latitude Regions of Saturn's Magnetosphere. Issue 12 (26th December 2017) - Davies, E. H.; Masters, A.; Dougherty, M. K.; Hansen, K. C.; Coates, A. J.; Hunt, G. J.
Abstract: Swept forward field is the term given to configurations of magnetic field wherein the field lines deviate from the meridional planes of a planet in the direction of its rotation. Evidence is presented for swept‐forward field configurations on Cassini orbits around Saturn from the first half of 2008. These orbits were selected on the basis of high inclination, spatial proximity, and temporal proximity, allowing for the observation of swept‐forward field and resolution of dynamic effects using data from the Cassini magnetometer. Nine orbits are surveyed; all show evidence of swept‐forward field, with typical sweep angle found to be 23°. Evidence is found for transient events that lead to temporary dramatic increases in sweep‐forward angle. The Michigan Solar Wind Model is employed to investigate temporal correlation between the arrivals of solar wind shocks at Saturn with these transient events, with two shown to include instances corresponding with solar wind shock arrivals. Measurements of equatorial electron number density from anode 5 of the Cassini Plasma Spectrometer instrument are investigated for evidence of magnetospheric compression, corresponding with predicted shock arrivals. Potential mechanisms for the transfer of momentum from the solar wind to the magnetosphere are discussed. Key Points: Field configurations at high‐latitude pre dusk magnetosphere are investigated at Saturn Swept forward field is found to be prevalent with an average angle of 23° Field is found to exhibit transient increases in sweep angle